THE EFFECT OF COMBINED ACUPUNCTURE AND PHYSIOTHERAPY ON PAIN INTENSITY DURING THE REHABILITATION PERIOD OF RHEUMATOID ARTHRITIS - Khojiyeva Nasiba O’ktam qizi; Abdullayev U.S. (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by joint inflammation, pain, and functional impairment, particularly during rehabilitation phases where pain management is crucial for improving quality of life. This study investigates the effect of combined acupuncture and physiotherapy on pain intensity in RA patients undergoing rehabilitation. A randomized controlled trial was conducted with 120 participants divided into three groups: combined acupuncture and physiotherapy (n=40), acupuncture alone (n=40), and physiotherapy alone (n=40). Pain intensity was measured using the Visual Analog Scale (VAS) at baseline, 4 weeks, and 8 weeks post-intervention. Results showed a significant reduction in VAS scores for the combined group (from 7.2 ± 1.5 to 3.1 ± 1.2, p<0.001) compared to individual therapies. The combined approach enhanced pain relief by 45% more than physiotherapy alone and improved joint function without adverse effects. This highlights the synergistic potential of integrating traditional and modern therapies for RA rehabilitation.